Duplication, balancing selection and trans-species evolution explain the high levels of polymorphism of the DQA MHC class II gene in voles (Arvicolinae) - Bryja, J; Galan, M; Charbonnel, N; Cosson, J F (Immunogenetics, 2006)
Major histocompatibility complex (MHC) genes play important role in host-parasite interactions and parasites are crucial factors influencing the population dynamics of hosts. We described the structure and diversity of exon 2 of the MHC class II DQA gene in three species of voles (Arvicolinae) exhibiting regular multi-annual fluctuations of population density and analysed the processes leading to the observed MHC polymorphism. By using cloning-sequencing methodology and capillary electrophoresis-single strand conformation polymorphism, we described seven sequences in the water, eight in the common, and seven in the bank voles coming from an area of 70 km(2) around the Nozeroy canton in the Jura Mountains (Franche Comté, France). All exon 2 sequences translate to give unique amino acid sequences and positive selection was found to act very intensively on antigen binding sites. We documented the presence of recombination at vole DQA region but its importance in generating allelic polymorphism seems to be relatively limited. For the first time within rodents, we documented the duplication of the DQA gene in all three species with both copies being transcriptionally active. Phylogenetic analysis of allelic sequences revealed extensive trans-species polymorphism within the subfamily although no alleles were shared between species in our data set. We discuss possible role of parasites in forming the recent polymorphism pattern of the DQA locus in voles.
Keywords: Animals; Base Sequence; Electrophoresis, Capillary; elektroforéza kapilární; sekvence aminokyselin; Genes, MHC Class II; Molecular Sequence Data; Polymorphism, Single-Stranded Conformational; HLA-DQ beta řetězec; Evolution, Molecular; molekulární evoluce; Amino Acid Sequence; Arvicolinae; Phylogeny; polymorfismus konformace jednovláknové DNA; molekulární sekvence - údaje; Cloning, Molecular; duplikace genu; geny MHC třídy II; sekvence nukleotidů; alely; Sequence Analysis, DNA; Alleles; klonování DNA; zvířata; sekvenční analýza DNA; HLA-DQ Antigens; fylogeneze; HLA-DQ antigeny; Gene Duplication; HLA-DQ beta-Chains